The accumulation of arsenic, uranium, and boron in Lemna gibba L. exposed to secondary effluents - Sasmaz, Ahmet; Obek, Erdal (Elsevier, 2009)
Aquatic plants are used as a practical and effective method to remove toxic elements from secondary-treated municipal wastewater. In this study, Lemna gibba was investigated for its capacity to remove uranium, arsenic, and boron from secondary effluents. L gibba was collected from a natural lake in Elazig, Turkey, then acclimatized to the effluent in situ. The concentration of toxic elements in the plant material was monitored as a function of time for 7 days. L. gibba significantly accumulated the toxic elements, particularly in the first 2 days. Arsenic, uranium, and boron were accumulated in the highest concentrations (133%. 122%, and 40%, respectively). However, in the following days, accumulation levels showed both increases and decreases, most probably due to L gibba reaching saturation levels. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bioaccumulation; Lemna gibba; Duckweed; Trace element; Secondary treatment; Municipal wastewater